Pengaruh Penilaian Kinerja Dan Budaya Organisasi Terhadap Motivasi Kerja Funding Officer Koperasi Artha Mandiri Abadi Cabang Cirebon - Iyustandi, Iyustandi (Mutiara: Multidiciplinary Scientifict Journal, 2024)
The problem in this study is the performance of funding officers in the form of savings Artha Mandiri Abadi Cirebon Cooperative does not reach the target every month. Even though from the initial survey research in terms of performance appraisal, motivation and organizational culture is quite good. This study aims to analyze the effect of performance appraisal and organizational culture on funding officer work motivation. This research is expected to be an input in the future development of cooperatives, especially those related to the performance of Artha Mandiri Abadi cooperative savings Cirebon branch. Respondents involved in this study were Funding Officer employees of Artha Mandiri Abadi cooperative, Cirebon branch, totaling 30 people. This type of research is descriptive and verification research